Clinical case. Large sized inflammated odontogenic cyst in a previously injured single lower incisor - Jorge N.r. Martins; Filipe Freitas; André Saudade; André Moreira; João Caramês (LLC "Endo Press", 2020)
One of the consequences of traumatic injuries is the chance of aseptic pulp necrosis to occur which in time may became infected and give origin to periapical pathosis. Although the apical granulomas and cysts are a common condition, there appearance as an extremely large radiolucent image is a rare finding. Differential diagnosis with other radiographic-like pathologies, such as keratocystic odontogenic tumour or unicystic ameloblastoma, is mandatory. The purpose of this paper is to report a very large radicular cyst caused by a single mandibular incisor traumatized long back, in a 60-year-old male. Medical and clinical histories were obtained, radiographic and cone beam CT examinations performed and an initial incisional biopsy was done. The final decision was to perform a surgical enucleation of a lesion, 51.4 mm in length. The enucleated tissue biopsy analysis was able to render the diagnosis as an inflammatory odontogenic cyst. A 2 year follow-up showed complete bone recovery.